2021
DOI: 10.1021/acs.jpca.1c05653
|View full text |Cite
|
Sign up to set email alerts
|

Stereodynamic Control of Collision-Induced Nonadiabatic Dynamics of NO (A2Σ+) with H2, N2, and CO: Intermolecular Interactions Drive Collision Outcomes

Abstract: Intermolecular interactions, stereodynamics, and coupled potential energy surfaces (PESs) all play a significant role in determining the outcomes of molecular collisions. A detailed knowledge of such processes is often essential for a proper interpretation of spectroscopic observations. For example, nitric oxide (NO), an important radical in combustion and atmospheric chemistry, is commonly quantified using laser-induced fluorescence on the A 2 Σ + ← X 2 Π transition band. However, the electronic quenching of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(52 citation statements)
references
References 44 publications
5
47
0
Order By: Relevance
“…The barrier separates the conical intersection of the D 1 and D 2 states from the region of the excited state readily accessed during a vertical electronic transition from the minimum N 2 −NO ground state geometry. 3 We also note that while the conical intersection may funnel population from the D 2 excited state to the D 1 state, it is not accessible at the energies in our current experiments due to the barrier. Finally, Guardado et al found that the minimum energy geometry for the (A 2 Σ + A′) excited state is linear with an R NN of 3.19 Å and a binding energy of 335.02 cm −1 .…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…The barrier separates the conical intersection of the D 1 and D 2 states from the region of the excited state readily accessed during a vertical electronic transition from the minimum N 2 −NO ground state geometry. 3 We also note that while the conical intersection may funnel population from the D 2 excited state to the D 1 state, it is not accessible at the energies in our current experiments due to the barrier. Finally, Guardado et al found that the minimum energy geometry for the (A 2 Σ + A′) excited state is linear with an R NN of 3.19 Å and a binding energy of 335.02 cm −1 .…”
Section: Introductionmentioning
confidence: 60%
“…3−5 In particular, a very recently published potential energy surface found the N 2 −NO (A) excited state to have a conical intersection that may funnel population to the ground state of the complex, leading to quenching. 3 The ground state for the N 2 −NO complex has been extensively studied using both electronic structure calculations and experiments. 4,6−10 The overall results for the ground state are consistent with relatively low barriers to internal rotation for the diatomic moieties, resulting in a floppy complex having a minimum geometry with the NO bond approximately perpendicular to the Jacobi vector between the NO center of mass (CM) and N 2 CM.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations